1978
DOI: 10.1136/hrt.40.4.421
|View full text |Cite
|
Sign up to set email alerts
|

Torsade de pointes ventricular tachycardia in a newborn infant.

Abstract: suMMARY A case of paroxysmal ventricular tachycardia of torsade de pointes variety occurring in a newborn infant is described. A rare problem in the newborn, ventricular tachycardia has been associated with congenital heart disease, electrolyte abnormality, and cardiac tumour. In this case, the association was with myocarditis. The arrhythmia was refractory to treatment, and the infant died.Ventricular tachycardia is unusual in children and even rarer in neonates (Addy and Littlewood, 1969;DeGuzman and Silver,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

1983
1983
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 10 publications
0
1
0
1
Order By: Relevance
“…Accordingly, in a large cohort of 186 patients with myocarditis, Ukena et al ( 16 ) demonstrated that a QTc prolongation ≥440 ms was frequent (~25% of cases) and predicted a poor clinical outcome, including cardiac death. Moreover, several cases of marked QTc prolongation complicated with TdP have been reported in patients with acute infective carditis (myo/endocarditis), independently from the specific etiologic agent involved ( 45 57 ). A peculiar form of diffuse myocarditis is Chagas’s disease, triggered by the protozoan Trypanosoma cruzi , and then progressing for (auto)immune-mediated mechanisms ( 58 ).…”
Section: Inflammation As a Cause Of Acquired Lqtsmentioning
confidence: 99%
“…Accordingly, in a large cohort of 186 patients with myocarditis, Ukena et al ( 16 ) demonstrated that a QTc prolongation ≥440 ms was frequent (~25% of cases) and predicted a poor clinical outcome, including cardiac death. Moreover, several cases of marked QTc prolongation complicated with TdP have been reported in patients with acute infective carditis (myo/endocarditis), independently from the specific etiologic agent involved ( 45 57 ). A peculiar form of diffuse myocarditis is Chagas’s disease, triggered by the protozoan Trypanosoma cruzi , and then progressing for (auto)immune-mediated mechanisms ( 58 ).…”
Section: Inflammation As a Cause Of Acquired Lqtsmentioning
confidence: 99%
“…Der jüngste Patient war ein Neugeborenes mit einem ange borenen AV-Block 3. Grades [29], der älteste ein 90jähriger [20]. Im Mittel waren die Patienten 61,7 ± (SD) 19,1 Jahre alt.…”
Section: Methodsunclassified